Antipyretic Activity of Ethanol Extract of Malay Apple Leaves (Syzygium malaccense L.) in Peptone-Induced Male White Rats (Rattus norvegicus) - Jeane Mongie; Rosalia V. Manti; Ferdy A. Karauwan; Silvana L. Tumbel; Nerni O. Potalangi; Rachmat Santoso; Christel N. Sambou (FMIPA UKIT, 2026)
Malay apple leaves (Syzygium malaccense L.) have traditionally been used to reduce fever. This study aimed to evaluate the antipyretic activity of the ethanol extract of Malay apple leaves in peptone-induced male white rats (Rattus norvegicus). A completely randomized design was used with five treatment groups: negative control (distilled water), positive control (paracetamol), and ethanol extract doses of 125, 250, and 500 mg/200 g body weight. Fever was induced by intramuscular injection of 5% peptone (1 mL/200 g body weight), and rectal temperature was recorded every 30 minutes for 180 minutes. Data were analyzed using Kruskal–Wallis followed by Mann–Whitney tests. The results showed that all extract doses reduced rectal temperature compared with the negative control, with the 500 mg dose producing the greatest antipyretic effect. Statistical analysis indicated significant differences among treatment groups (p < 0.05). In conclusion, the ethanol extract of Malay apple leaves possesses antipyretic activity in peptone-induced male white rats, with the 500 mg dose showing the highest effectiveness.